2016
DOI: 10.1002/2015ja022073
|View full text |Cite
|
Sign up to set email alerts
|

Europa's far ultraviolet oxygen aurora from a comprehensive set of HST observations

Abstract: We analyze a large set of far ultraviolet oxygen aurora images of Europa's atmosphere taken by Hubble's Space Telescope Imaging Spectrograph (HST/STIS) in 1999 and on 19 occasions between 2012 and 2015. We find that both brightness and aurora morphology undergo systematic variations correlated to the periodically changing plasma environment. The time variable morphology seems to be strongly affected by Europa's interaction with the magnetospheric plasma. The brightest emissions are often found in the polar reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
133
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 61 publications
(159 citation statements)
references
References 68 publications
24
133
0
Order By: Relevance
“…At higher altitudes, the relative abundance of the lighter species (O, H 2 O, OH, H 2 , H) increases compared to O 2 (Shematovich et al 2005;Smyth & Marconi 2006), which was observationally confirmed for atomic oxygen O (Hansen et al 2006;Roth et al 2016). The Monte Carlo simulations by Shematovich et al (2005) and Smyth & Marconi (2006) further suggest that the escape of hydrogen, in particular H 2 , is higher than the oxygen escape and that hydrogen is, therefore, the main species forming the neutral torus that was detected near Europa (Lagg et al 2003;Mauk et al 2003).…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…At higher altitudes, the relative abundance of the lighter species (O, H 2 O, OH, H 2 , H) increases compared to O 2 (Shematovich et al 2005;Smyth & Marconi 2006), which was observationally confirmed for atomic oxygen O (Hansen et al 2006;Roth et al 2016). The Monte Carlo simulations by Shematovich et al (2005) and Smyth & Marconi (2006) further suggest that the escape of hydrogen, in particular H 2 , is higher than the oxygen escape and that hydrogen is, therefore, the main species forming the neutral torus that was detected near Europa (Lagg et al 2003;Mauk et al 2003).…”
Section: Introductionmentioning
confidence: 68%
“…The cross-section of the primary atmospheric constituent, O 2 , reaches the highest values at the observed FUV wavelengths near 1244.4 and 1205.4 Å, and at the SchumannRunge continuum above ∼1300 Å (Ogawa & Ogawa 1975;Lu et al 2010). At 1216 Å (Lyα) the cross-section assumes a lower value of ∼1×10 −20 cm 2 (Ogawa 1968 (Hall et al 1998;Roth et al 2016), which corresponds to a maximum line-of-sight column density of , or a transmittance of >99.9%. Hence, although O 2 is the dominant species, there is no absorption by it at the Lyα.…”
Section: Estimation Of the Optical Depth And Emission Contributionsmentioning
confidence: 97%
“…The higher sensitivity of the HST Cosmic Origins Spectrograph (COS) later allowed the detection of faint oxygen emission of a few rayleighs [ Cunningham et al , ], suggesting an O 2 column density of ∼4 × 10 15 cm −2 on the leading/Jupiter‐facing hemisphere. This column density is 5 times larger than the CO 2 column density and approximately 1 order of magnitude larger than the O 2 column densities at Ganymede and Europa [ Hall et al , ; Roth et al , ].…”
Section: Introductionmentioning
confidence: 95%
“…Though the exosphere of Europa arises from material escaping from the surface, its basic properties such as areal coverage, density, thermal structure, and spatial and temporal variability are poorly understood (McGrath et al, 2009;Roth et al, 2015).…”
Section: Introductionmentioning
confidence: 99%